The Hybridization of Islamic Education Management in the Integration of a Collaborative-Based Pesantren Curriculum - Mubarok, Ikhsan; Nadhir, Mirhabun (Dirasah International Journal of Islamic Studies, 2025)
This study examines the practice of hybridization in Islamic education management through the integration of a collaborative-based curriculum in pesantren, as well as its implications for educational governance, the roles of key actors, and the development of students’ competencies. This research employs a descriptive qualitative approach with a case study design conducted at Pondok Pesantren Salafiyah Asy-Syafi’iyyah Darul Qur’an. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the hybridization of educational management contributes to the emergence of participatory collaborative governance, the development of an adaptive living curriculum, and the repositioning of teachers as knowledge brokers within a collaborative learning network. In addition, students demonstrate enhanced competencies that integrate religious understanding, collaborative skills, and contextual awareness. The study also identifies a dynamic interplay between traditional authority and open collaboration, which is continuously negotiated through adaptive processes. This research contributes to the development of hybridization as an integrative framework in Islamic education management that bridges tradition and innovation in a sustainable manner.